Genomic and personalized medicine - Ginsburg, Geoffrey S.; Willard, Huntington F. (Elsevier/Academic Press, 2013)
This two-volume set provides an in-depth look at one of the most promising avenues for advances in the diagnosis, prevention and treatment of human disease. The inclusion of the latest information on diagnostic testing, population screening, predicting disease susceptibility, pharmacogenomics and more presents this book as an essential tool for both students and specialists across many biological and medical disciplines, including human genetics and genomics, oncology, neuroscience, cardiology, infectious disease, molecular medicine, and biomedical science, as well as health policy disciplines focusing on ethical, legal, regulatory and economic aspects of genomics and medicine. Volume One Includes: Principles, Methodology and Translational Approaches, takes readers on the journey from principles of human genomics to technology, informatic and computational platforms for genomic medicine, as well as strategies for translating genomic discoveries into advances in personalized clinical care. Volume Two Includes: Genome Discoveries and Clinical Applications presents the latest developments in disease-based genomic and personalized medicine. With chapters dedicated to cardiovascular disease, oncology, inflammatory disease, metabolic disease, neuropsychiatric disease, and infectious disease, this work provides the most comprehensive guide to the principles and practice of genomic and personalized medicine. * Contributions from leaders in the field provide unparalleled insight into current technologies and applications in clinical medicine. * Full colour throughout enhances the utility of this work as the only available comprehensive reference for genomic and personalized medicine. * Discusses scientific foundations and practical applications of new discoveries, as well as ethical, legal/regulatory, and social issues related to the practice of genomic medicine.